Identifying strategies to assist final semester nursing students to develop numeracy skills: A mixed methods study - Ramjan, Lucie M.; Stewart, Lyn; Salamonson, Yenna; Morris, Maureen M.; Armstrong, Lyn; Sanchez, Paula; Flannery, Liz (Nurse education today, 2014)
It remains a grave concern that many nursing students within tertiary institutions continue to experience difficulties with achieving medication calculation competency. In addition, universities have a moral responsibility to prepare proficient clinicians for graduate practice. This requires risk management strategies to reduce adverse medication errors post registration. To identify strategies and potential predictors that may assist nurse academics to tailor their drug calculation teaching and assessment methods. This project builds on previous experience and explores students' perceptions of newly implemented interventions designed to increase confidence and competence in medication calculation. This mixed method study surveyed students (n=405) enrolled in their final semester of study at a large, metropolitan university in Sydney, Australia. Tailored, contextualised interventions included online practice quizzes, simulated medication calculation scenarios developed for clinical practice classes, contextualised ‘pen and paper’ tests, visually enhanced didactic remediation and ‘hands-on’ contextualised workshops. Surveys were administered to students to determine their perceptions of interventions and to identify whether these interventions assisted with calculation competence. Test scores were analysed using SPSS v. 20 for correlations between students' perceptions and actual performance. Qualitative open-ended survey questions were analysed manually and thematically. The study reinforced that nursing students preferred a ‘hands-on,’ contextualised approach to learning that was ‘authentic’ and aligned with clinical practice. Our interventions assisted with supporting students' learning and improvement of calculation confidence. Qualitative data provided further insight into students' awareness of their calculation errors and preferred learning styles. Some of the strongest predictors for numeracy skill performance included (1) being an international student, (2) completion of an online practice quiz, scoring 59% or above and (3) students' self-reported confidence. A paradigm shift from traditional testing methods to the implementation of intensive, contextualised numeracy teaching and assessment within tertiary institutions will enhance learning and promote best teaching practices.